NALURI KEHIDUPAN DAN NALURI KEMATIAN DALAM FILM NEVER LET ME GO KARYA KAZUO ISHIGURO - Abi Ihsanullah; Badri Badri; Muhammad Fathan Zamani (Universitas Aki, 2022)
All living things have instincts. Every living thing has the instinct to survive and the instinct to die. The objectives of the research are to analyze the film entitled Never Let Me Go by Kazuo Ishiguro using Sigmund Freud's Psychoanalysis theory and the stages of grief’s theory using Kubler Ross’s perspective. The researcher will focus on the actions taken by Kath, Ruth, and Tommy by explaining the life instincts and death instincts according to Sigmund Freud’s theory and the stages of grief experienced by Tommy using Kubler Ross's theory. This research uses a material object in the form of the film entitled Never Let Me Go by Kazuo Ishiguro and a formal object in the form of the theory of life and death instinct according to Sigmund Freud’s perspective and stage of grief according to Kubler Ross’s perspective. This research applies the qualitative descriptive method. The findings are as follows: life instinct is carried out by Kathy and death instincts are carried out by Ruth and Tommy. In addition, the stages of grief experienced by Tommy are as follows: (1) denial, (2) anger, (3) bargaining, (4) depression, and (5) acceptance.